2015
DOI: 10.3923/ajcn.2015.64.75
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Determined by Different Measures and its Impact on the Health-Related Quality of Life of Young-Adult Nigerians

Abstract: The prevalence of overweight/obesity is rising in developing countries yet their effects on the Quality Of Life (QOL) of Nigerians have not been assessed. This study therefore investigated the prevalence of obesity determined by different tools and their effects on the QOL of young Nigerians. Internationally accepted protocols were employed for the anthropometric diagnosis of obesity while the percentage body fat was estimated using a bioelectrical impedance analysis device. The QOL of the subjects were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Central obesity was defined as WC>88cm for women and >102cm for men; WHR ≥0.90 for men and ≥0.85 [8]. Excess body fat was defined as percentage body fat ≥32.0% (females) and ≥21.7% (males) [9][10][11]. Hypertension was defined as BP ≥140/90mmHg [12].…”
Section: Data Collectionmentioning
confidence: 99%
“…Central obesity was defined as WC>88cm for women and >102cm for men; WHR ≥0.90 for men and ≥0.85 [8]. Excess body fat was defined as percentage body fat ≥32.0% (females) and ≥21.7% (males) [9][10][11]. Hypertension was defined as BP ≥140/90mmHg [12].…”
Section: Data Collectionmentioning
confidence: 99%
“…Low and middle income countries (LMICs) are thought to be experiencing increases in the obesity epidemic that match, or in some cases surpass, those of some high income countries. A recent study in young-adult Nigerians reported overweight/obesity in 17% of the population (13% for males and 20.9% for females) (Ejike et al 2015). A slightly earlier study in adult Nigerians (AkaroloAnthony et al 2014) reported significantly higher values [64% (74% for women and 57% for men)].…”
Section: Introductionmentioning
confidence: 95%
“…We also found a clear female preponderance of overweight/obesity in the studied population. A recent study among young adults found that a total of 17% of the population (13% for males and 20.9% for females) were overweight/obese according to the BMI diagnostic criteria [ 19 ]. A slightly earlier study in young adults had reported a prevalence of 20.7% (17.5% for males; 24.8% for females) for overweight/obesity using the same standards [ 20 ].…”
Section: Discussionmentioning
confidence: 99%